Study on Entreprenuership Development in SD Kanisius Protakan, Ngargomulyo, Muntilan - Betti Arriati (Journal of Management and Business Environment (JMBE), 2019)
This paperaims to describe and understand how entrepreneurship was developed in SD Kanisius Protakan, Ngargomulyo, Muntilan. It was intended to build entrpernuerial characteristics in early childhood based on ecology and local wisdom. Entrepreneurship included in this learning process was in the form of respecting farmers as a dignified job because they take role in supporting human welfare and respecting the universe that has provided fertility and diversity of resources that can help humans improve their standard of living. This awareness needs to be developed so that children are proud of themselves, their parents, and their environment.They can thus grow into individuals who are ready to have entrepreneurial spirit for creatively and innovatively can utilize natural resources and humans to work together for mutual prosperity. Collaboration needed through parents, school and communities will provide a variety of ways of learning through parents, teachers and the community who remain rooted in local culture.